'We thought she was a witch': Gender, class and whiteness in the familial 'memory archive'. (April 2023) - Hemmings, Clare
'We thought she was a witch' uses my own 'memory archive' to give texture to the complex inheritance of gender, class and race that characterises the present. Drawing on interviews, archival data and fictionalisation, the article explores the role of gendered labour in securing dominant understandings of class progress. Starting from stories, my mother and I weave together of the history of 64 Chepstow Road, Newport (where her maternal family lived), I highlight the cost of historiography that does not pay attention to what is written out of family memory. The article draws on existing feminist memory work to flesh out an intersectional approach to the 'memory archive' we inherit and introduces the importance of an imaginative approach to the past.